Volba determinantů v nominální anafoře — srovnání situace ve španělštině a češtině : The Choice of Determiners in Nominal Anaphora — Comparison of Usage in Spanish and Czech - Adéla Erbenová (Časopis pro Moderní Filologii, 2016)
This study deals with issues of determiners in different types of nominal anaphora in Spanish and Czech. It analyzes the choice between demonstratives and the definite article in Spanish. As there is no definite article in Czech, speakers choose between demonstratives and the noun without any determiner. Our goal is to identify the factors that influence the choice of determiners in both languages and the similarities and differences between them. The results show that the situation in both languages is complex and that the definite article in Spanish sometimes corresponds to the null-determiner in Czech and sometimes to a demonstrative.